Factors influencing the immunogenicity of influenza vaccines. Issue 8 (3rd August 2021) - Wen, Simin; Wu, Zhengyu; Zhong, Shuyi; Li, Mao; Shu, Yuelong
ABSTRACT: Annual vaccination is the best prevention of influenza. However, the immunogenicity of influenza vaccines varies among different populations. It is important to fully identify the factors that may affect the immunogenicity of the vaccines to provide best protection for vaccine recipients. This paper reviews the factors that may influence the immunogenicity of influenza vaccines from the aspects of vaccine factors, adjuvants, individual factors, repeated vaccination, and genetic factors. The confirmed or hypothesized molecular mechanisms of these factors have also been briefly summarized.